Sindrome de burnout en enfermeras del Hospital General de Durango y Hospital Regional Docente de Trujillo, 2014 - Asmat Ortiz, Nataly Wendy (2015)
The current study was performed in order to compare the Burnout Syndrome(SB) level according to the dimensions: emotional exhaustion(AE), depersonalization(DP) and personal success(RP) in nurses who work at Hospital General de Durango(HGD)-Mexico and Hospital Regional de Trujillo(HRDT)-Peru, 2014. The sample was made by 61 nurses who work at HRDT and 170 nurses who work at HGD, who were asked the Maslach Burnout Inventory (MBI) questionnaire. The results were analyzed trough by the statistic package vs 19.0. To determine if an important difference exists, the U Mann-Whitney statistic probe was used and the results were that: 54.7% and 57,4% of HGD and HRDT showed a mid-level of SB according to AE, respectively; 80,6% and 70,5% of nurses of HGD and HRDT showed a mid-level of SB according to dimension DP, respectively; finally, 48,8% and 62,3% of nurses of HGD and HRDT showed a mid-level of SB according to dimension RP, respectively. It is concluded that according to dimensions AE and DP, there are important differences between both hospitals, whereas according to dimension RP, important differences were not found between both hospitals.